Preservação e renovação: o caso da avenida Brasil - Oliveira, Luis Fernando Correa Santos de (2006)
The present work is about preservation and renewal of uses in protected historic urban settings, studying the case of Avenida Brasil in São Paulo, by means of data regarding the avenue and its surrounding area - the Jardim América garden suburb - its historical context, precedents, concepts, projects etc., reaching its current conformation. Based on existing bibliography, on the analysis of urban legislation and considerable iconographic material, an analysis is proposed of Avenida Brasil, an importante element of the city's landscape, environment, urban and architectural heritage, a remnant of the prestigious residential avenues created in São Paulo, whose physical characteristics are preserved, despite the completely diverse context that has arisen since the time of its implantation.